Emotions: A very short introduction - Evans, Dylan (Oxford Oxford university press, 2003)
Was love invented by European poets in the Middle Ages or is it part of human nature? Will winning the lottery really make you happy? Is it possible to build robots that have feelings? These are just some of the intriguing questions explored in this guide to the latest thinking about the emotions. Drawing on a wide range of scientific research, from anthropology and psychology to neuroscience and artificial intelligence, Emotion: The Science of Sentiment takes the reader on a fascinating journey into the human heart.